1996
DOI: 10.1016/0009-8981(96)06281-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum alkaline phosphatase activity during zinc deficiency and long-term inflammatory stress

Abstract: A decrease in serum zinc can be caused by a real zinc deficiency but can also be caused by an apparent zinc deficiency, e.g. in inflammatory stress. The aim of this study was to evaluate the diagnostic power of serum alkaline phosphatase (AP) activity in the discrimi nation between pathophysiologic states of "real" and "apparent" zinc deficiency. A decrease in serum zinc was induced in growing and adult rats, by providing a diet low in zinc and by causing inflammatory stress. AP activity was determined using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Serum alkaline phosphatase measurement has been suggested as an important surrogate marker of zinc status in human [14]. In present study, it has been shown that serum alkaline phosphatase was low in all patients, may be correlating with zinc deficiency, but we were not able to do the follow up study on the seventh and fourteenth day supplementation.…”
Section: Discussionmentioning
confidence: 55%
“…Serum alkaline phosphatase measurement has been suggested as an important surrogate marker of zinc status in human [14]. In present study, it has been shown that serum alkaline phosphatase was low in all patients, may be correlating with zinc deficiency, but we were not able to do the follow up study on the seventh and fourteenth day supplementation.…”
Section: Discussionmentioning
confidence: 55%
“…Serum alkaline phosphatase measurement has been suggested as an important surrogate marker of zinc status in humans. 37,38 The serial rise of serum alkaline phosphatase values in supplemented children suggests that sufficient absorption and replenishment of body zinc occurred with the dose of zinc used.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24] Because zinc deprivation Data are expressed as mean ± SD, n = 10. [25][26][27] Hence, the ALP activity is a good indicator to evaluate the status of zinc deficiency in growing rats. † Difference from the PF group, P < 0.05.…”
Section: Discussionmentioning
confidence: 99%